Uji Efektivitas Salep Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) pada Kelinci (Oryctolagus cuniculus) yang Terinfeksi Bakteri Staphylococcus aureus - Paju, Niswah; Yamlean, Paulina V.Y.; Kojong, Novel (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT Binahong leaf as traditional medicine possess antibacterial activity. The aims of this research were to study the effectivity of Binahong (Anredera cordifolia (Ten.) Steenis) leaf extract ointment on wound infected with Staphylococcus aureus, and to study the differences effectivity of Binahong leaf extract ointment (Anredera cordifolia (Ten.) Steenis) as antibacterial with concentration 10%, 20% and 40%. This research using laboratory experimental method. The subjects in these research were 5 rabits which divided into 5 groups, namely negative control, positive control and treatments group with concentration 10%, 20% and 40% of Binahong leaf extract ointment. Rabits back were wounded 2,5 cm and infected with Staphylococcus aureus. Research and statistical results shows that Binahong leaf extract ointment possess wound healing effectivity to the wound infected with Staphylococcus aureus. At concentration 10%, it already exhibit healing effectivity, although concentration 20% and 40% shows more healing effectivity. The increases of concentration of Binahong leaf extract ointment effectively heal the wound infected with Staphylococcus aureus. Â Key words : Binahong (Anredera cordifolia (Ten.) Steenis), ointment, extract, wound healing, rabit.